Study of the decay B[bar]0→Λ+cp[bar]π+π- and its intermediate states - Lees, Jean-Pierre; Adametz, Aleksandra; Uwer, Ulrich (Physical review. D, Particles, fields, gravitation, and cosmology, 2013)
We study the decay ¯¯¯B0→Λ+c¯pπ+π−, reconstructing the Λ+c baryon in the pK−π+ mode, using a data sample of 467×106 B¯¯¯B pairs collected with the BABAR detector at the PEP-II storage rings at SLAC. We measure branching fractions for decays with intermediate Σc baryons to be B[¯¯¯B0→Σc(2455)++¯pπ−]=(21.3±1.0±1.0±5.5)×10−5, B[¯¯¯B0→Σc(2520)++¯pπ−]=(11.5±1.0±0.5±3.0)×10−5, B[¯¯¯B0→Σc(2455)0¯pπ+]=(9.1±0.7±0.4±2.4)×10−5, and B[¯¯¯B0→Σc(2520)0¯pπ+]=(2.2±0.7±0.1±0.6)×10−5, where the uncertainties are statistical, systematic, and due to the uncertainty on the Λ+c→pK−π+ branching fraction, respectively. For decays without Σc(2455) or Σc(2520) resonances, we measure B[¯¯¯B0→Λ+c¯pπ+π−]non−Σc=(79±4±4±20)×10−5. The total branching fraction is determined to be B[¯¯¯B0→Λ+c¯pπ+π−]total=(123±5±7±32)×10−5. We examine multibody mass combinations in the resonant three-particle Σc¯pπ final states and in the four-particle Λ+c¯pπ+π− final state, and observe different characteristics for the ¯pπ combination in neutral versus doubly charged Σc decays.